Answer:
y = 3x -√2
Explanation:
You want the tangent to the curve defined by x²(x² +y²) = y² at the point (√2/2, √2/2).
Slope
The slope of the tangent line is the derivative of the function at that point. The given equation can be rearranged to ...
y² = x⁴/(1 -x²)
Then the derivative is ...
2yy' = ((1 -x²)(4x³) -(x⁴)(-2x))/(1 -x²)²
Dividing by 2y gives ...
Evaluating this expression at x=√2/2, we find the slope to be ...
Point-slope equation
The point-slope equation of the tangent line is ...
y -k = m(x -h) . . . . . . . . line with slope m through point (h, k)
y -√2/2 = 3(x -√2/2) . . . . line with slope 3 through point (√2/2, √2/2)
Rearranging to slope-intercept form, we get ...
y = 3x -3√2/2 +√2/2 . . . . . eliminate parentheses, add √2/2
y = 3x -√2 . . . . . . . . . . . . collect terms
__
Additional comment
We noticed that the given point (√3/2, √3/2) does not satisfy the equation, so we went looking for a point on the line y=x that does satisfy the equation. We found that (√2/2, √2/2) is on the graph, so we suspect a typo in the original problem statement. This answer gives the equation of the tangent line through the point (√2/2, √2/2).